Peningkatan Pembelajaran Fiqh Ibadah Dengan Menerapkan Metode Demonstrasi Di Kelas Vii C SMP Muhammadiyah 6 Surakarta Tahun Pelajaran 2016/2017 - Lestari, Dewi, Bambang Raharjo, Drs, M. Ag (2017)
This research aims to prove and describe that the demonstration method can increase the outcomes of learning fiqh ibadah especially in the material of shalat (praying). This research uses the method of experiment, altough it is conducted in the similar sample, but the treatment on the objects is different. The objects in this research were the method of speech and the method of demonstrasion. The technique of data collection used the method of experiment, test, observation, and documentation in order to obtain the assessment data either from the written test or the practice test. Meanwhile, the technique of data analysis uses "t" test. The initial data in this research are the scores of the outcomes of shalat practice in the time of implementing the method of speech. Then, the data were compared to the assessment outcomes of shalat practice in the time of implementing the method of demonstration. The both results were calculated and found the D (Difference) between the variabel score X (the method of speech) and the Variable Y (the method of demonstration) using the formula: D = X-Y. Based on the result of the test obtained, it is found that the difference between two scores of variable is D : -123. Then the result of the difference is added therefore, it is obtained ΣD. The result of ΣD = 757. After conducting calculation in order to obtain "t" value in order to test the truth/falsehood of the null hypotesis, then the result of t∘ (t count) was 9,781. By comparing the quantity of "t" that we obtained in the calculation (t∘= 9,781) and the quantity of "t" listed on the Table of "t" Value (tt.ts.5% = 2,06 and tt.ts. 1% = 2,80 therefore, we can know that t∘ is bigger than tt that is: 2,06 < 9,781 > 2,80. Because t∘ is bigger than tt, the Null Hypothesis previously proposed is rejected; it means that there is an increase in the outcomes of learning the fiqh ibadah between the time before implementing the method of demonstration and after implementing the method of demonstration, so there is a significant difference. This research also used the method of observation to complete the data of count analysis. The method of observation is conducted in the time of observing the shalat practice by implementing the method of speech and the method of demonstration. The results of the observation are then compared. The result of the observation is that the method of demonstration has been better than the method of speech. In the time of implementing the method of speech, the students shalat movement had not been perfect, then by implementing the method of demonstration, it could improve the imperfect shalat movement. Based on the above explanation, it can be concluded that the method of demonstration can increase the outcomes of learning fiqh ibadah especially in the material of shalat. Therefore, the researcher gives suggestion to consider the method of demonstration as one of methods that can increase the outcome of learning fiqh ibadah.